Strategi Trimurti Dalam Mewujudkan Mimpi Besar Dalam Mencetak Kepemimpinan Di Indonesia - Yusuf Adi Prianto; Hilalludin Hilalludin; Adi Haironi (Universitas Palangka Raya, 2024)
In the 20th century, Indonesia underwent significant social and political transformations. Trimurti, consisting of KH Imam Zarkasyi, KH Ahmad Sahal, and KH Zainuddin Fanani, emerged as central figures in shaping religious values and fostering self-reliance in Indonesia. They played pivotal roles in Islamic education at Pondok Modern Darussalam Gontor, emphasizing the importance of integrity and commitment in leadership and community building. This literature review-based research investigates Trimurti's thoughts and contributions within the contexts of education and leadership. The findings reveal that their approach reinforced Islamic educational traditions, teaching values of simplicity, self-reliance, and community service. Trimurti not only produced skilled religious scholars but also leaders prepared to confront global challenges. This study provides insights into how Islamic education and religious values can shape resilient character and leadership in society. The implications of Trimurti's approach underscore the importance of holistic education in cultivating integrity-driven leaders capable of advancing the nation.